2011
DOI: 10.1175/2011jhm1358.1
|View full text |Cite
|
Sign up to set email alerts
|

Flooding in Western Washington: The Connection to Atmospheric Rivers*

Abstract: This study utilizes multiple decades of daily streamflow data gathered in four major watersheds in western Washington to determine the meteorological conditions most likely to cause flooding in those watersheds. Two are located in the Olympic Mountains and the other two in the western Cascades; and each has uniquely different topographic characteristics. The flood analysis is based on the maximum daily flow observed during each water year (WY) at each site [i.e., the annual peak daily flow (APDF)], with an ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
284
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(308 citation statements)
references
References 34 publications
15
284
2
Order By: Relevance
“…The magenta line A-B defines a cross-section projection for (3). The pink segments over the pre-cold-frontal LLJ (with a-b) marked the limits with profiles for (2) fields) to determine whether an AR caused the extremes (e.g., Ralph et al, 2006;Lavers et al, 2011;Neiman et al, 2011).…”
Section: Methods To Identify Atmospheric Riversmentioning
confidence: 99%
“…The magenta line A-B defines a cross-section projection for (3). The pink segments over the pre-cold-frontal LLJ (with a-b) marked the limits with profiles for (2) fields) to determine whether an AR caused the extremes (e.g., Ralph et al, 2006;Lavers et al, 2011;Neiman et al, 2011).…”
Section: Methods To Identify Atmospheric Riversmentioning
confidence: 99%
“…ARs are plumes of intense tropospheric water vapor transport that often result in weather and/or hydrologic extremes (e.g., heavy rainfall, flash floods) upon landfall. [22][23][24][25] Repeated landfalling ARs or a complete lack thereof may result in periods of precipitation abundance or drought for regions along the west coast of North America. 26,27 Several studies suggest the potential for skillful subseasonal prediction based on observed relationships between the MJO and AR activity.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, however, that at subbasin scales, and/or in combination with an appropriate soil moisture indicator, some measure of rainfall might prove useful for predicting localized flooding. This has been a valuable strategy for APF/APD hindcasting in nival-pluvial and pluvial catchments (Neiman et al, 2011;Surfleet and Tullos, 2013). …”
Section: Resultsmentioning
confidence: 99%